The Role of Gender-Responsive PTKIS in Women's Career Development - Aziza Meria; Radhiatul Hasnah; Lukmanul Hakim; Rezki Amelia; Ruri Afria Nursa (TSAQAFAH, 2023)
This study aims to describe the role of gender-responsive PTKIS in developing the careers of female educators and education personnel in West Sumatra. The development of women's employment in PTKIS is one form of proof that gender equality between men and women is the basis of Islamic teachings. Gender equality is a condition of equal access and participation, control and benefits in development in all areas of life. Gender equality in career development here is equality in social strata, namely in terms of providing access, employment, wages and others. For this reason, the role of PTKIS in developing women's careers is needed. This research is field research using a qualitative approach. Data collection was done with in-depth interviews, observation, and documentation. Data analysis was carried out with narrative and descriptive analysis. The results showed that women's career development, namely in occupying positions at PTKIS West Sumatra, was initially quantitatively quite good, but in the last 2 years, it has decreased. Planning and program activities and infrastructure that can support women's career development are minimal, gender subordinates by women themselves/still limiting themselves, and the stereotype of women's leadership. Then, the efforts made by PTKIS in developing women's careers are by providing opportunities for training and continuing education to a higher level, providing flexible time according to the conditions of women determining teaching and office schedules, and providing opportunities for women to have careers/jobs outside the institution.